Risk Stratification in Twin Pregnancies Complicated by GDM - Anja Catic; Florian Heinzl; Christian Göbl; Gülen Yerlikaya-Schatten; Theresa Reischer (Journal of Diabetes Research)
Conclusion: Identifying threshold values for insulin therapy and risk stratification in twin pregnancy are crucial for optimal patient management.